Real-Time Detection of Periforaminal Vessels in the Cervical Spine: An Ultrasound Survey. Issue 2 (March 2016) - Finlayson, Roderick J.; Etheridge, John-Paul B.; Chalermkitpanit, Pornpan; Tiyaprasertkul, Worakamol; Nelems, Bill; Tran, De Q.H.; Huntoon, Marc A.
Abstract : Background and Objectives: Compared with the thoracic and lumbar spine, transforaminal epidural injections and medial branch blocks in the cervical spine are associated with a higher incidence of neurological complications. Accidental breach of small periforaminal arteries has been implicated in many instances. In this observational study, using ultrasonography, we surveyed the incidence of periforaminal bloods vessels in the cervical spine. Methods: Patients undergoing ultrasound-guided cervical medial branch blocks were scanned using color power and pulsed wave Doppler. Five levels from C2/C3 to C6/C7 were studied. Incidental blood vessels located between the anterior tubercles of the transverses process and the posterior borders of the articular pillars were included for analysis. We recorded the diameter and position of arteries relative to contiguous bony landmarks as well the number of veins. Results: In 102 patients, we performed a total 201 scans (1005 cervical levels). Of the 363 incidental vessels identified, 238 were arteries (mean diameter, 1.25 ± 0.45 mm). The latter were most commonly found at the posterior foraminal aspects of C5, C6, and C7 (13%, 11%, and 16% of scans, respectively); the transverse processes of C5 and C6 (10% and 16% of scans, respectively); and the articular pillars of C6 and C7 (19% and 16% of scans, respectively). Conclusions: Small periforaminal arteries are prevalent along the lateral aspect of the cervical spine, adjacent to areas commonly targeted by nerve block procedures. Further trials are required to determine if ultrasound guidance can reduce the incidence of complications related to accidental vascular breach.